The Everyday Life of Patients With Tuberculosis in the Concentration Camp of Mittelbau-Dora (1943–1945) - Kiosze, Philipp; Steger, Florian (Frontiers in Medicine, 2020)
The everyday life of patients with tuberculosis in the main prisoner infirmary of the Mittelbau-Dora concentration camp is analyzed historically-critically by medical records, documents of the Schutzstaffel (SS) physicians, contemporary medical textbooks and memoirs of former inmates from partly international archives. To compare the medical treatment in the three phases of the concentration camp, the representative months of February 1944, July 1944 and January 1945 were examined. The analysis shows that SS hygienists inspected the place for fear of a collapse of the V-2 rocket production. The primitive medical infrastructure was slowly expanded after its founding in 1943. SS physicians and medics led and supervised the treatment provided by inmates. These were in an ethical dilemma between cooperation with the SS and commitment to the sick prisoners. The Tuberculosis Department was used for isolation. Sputum diagnostics and X-ray equipment were utilised as selection tools. Infectious patients laid usually for weeks in the same bed with two other patients. Significantly more resources were available, however, for non-infectious tuberculosis patients. The therapy was based on the medical expert opinion of the time and was mainly symptomatic such as fever reduction. Rest and vitamins should make prisoners fit for the armament industry. Patients with tuberculosis had a high death rate. The prisoners who survived were discharged, but often did not recover. Several thousand prisoners were selected for transports, which led to special concentration camps for seriously ill prisoners (Lublin-Majdanek, Bergen-Belsen) and the subcamp Boelcke-Kaserne. There, they often died of catastrophic conditions or were killed.